Risk management in student affairs foundations for safety and success - Miller, Thomas E. 1948 November 25-; Sorochty, Roger W. (San Francisco, CA Jossey-Bass, 2015)
"A comprehensive, accessible guide to the policies and practices of risk management in higher education. Helps practitioners understand the sources of risk in their work, and the practices and strategies they can employ to help mitigate that risk. Topics include Tort liability, contracts, state and federal violations, and resource protection"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Student affairs services -- United States -- Administration; Universities and colleges -- United States -- Administration; Education, Higher -- United States -- Administration; Education, Higher -- Law and legislation -- United States; Schools -- Risk management -- United States; College administrators -- United States -- Handbooks, manuals, etc